CLA improves the lipo-nutritional quality of pork and regulates the gut microbiota in Heigai pigs. Issue 23 (15th November 2022) - Wang, Liyi; Zhang, Shu; Huang, Yuqin; You, Wenjing; Zhou, Yanbing; Chen, Wentao; Sun, Ye; Yi, Wuzhou; Sun, Houwei; Xie, Jintang; Zhu, Xiaodong; Zheng, Qiankun; et al.
Abstract : CLA improves the lipo-nutritional quality in muscle and these changes are associated with the production and functions of differential bacteria and SCFAs in the gut of Heigai pigs. Abstract : Conjugated linoleic acid (CLA) is a potential nutritional strategy to regulate meat quality in pigs and produce high-quality pork. However, the effects of CLA on nutritional quality, lipid dynamics, microbiota, and their metabolites in the gut of pigs remain unclear. Our study explored the effects of CLA on lipo-nutritional quality based on a Heigai pig model and investigated the regulatory mechanism using an integrated analysis of multiple omics. A total of 58 Heigai finishing pigs (body weight: 85.58 ± 10.39 kg) were randomly divided into 2 treatments and fed diets containing 1% soyabean oil and 1% CLA for 40 days. 1% CLA significantly decreased the backfat thickness ( P < 0.05) and increased the intramuscular fat (IMF) content ( P < 0.05). The expression of lipid metabolism-related genes was significantly changed ( P < 0.05) and lipidome analysis showed the alternations of lipid dynamics in the longissimus dorsi muscle (LDM). In addition, based on the microbiome and metabolomic analyses, the relative abundances of Parabacteroides, Bacteroides, and Lachnospiraceae_UCG-010 increased and CLA changed the metabolome profiles and the short-chain fatty acid (SCFA) composition in the gut, which were significantly increased ( P < 0.05). Additionally, Pearson's correlation analysis indicated that differential microbial genera and SCFAs induced by CLA had tight correlations with the backfat thickness, IMF content and lipids in the LDM. CLA enhances the lipid accumulation and metabolism in muscle and these changes are associated with the production and functions of the differential bacteria and SCFAs in the gut of pigs.